Multiplexed Genome Editing via an RNA Polymerase II Promoter-Driven sgRNA Array in the Diatom Phaeodactylum tricornutum: Insights Into the Role of StLDP - Taparia, Yogesh; Dolui, Achintya Kumar; Boussiba, Sammy; Khozin-Goldberg, Inna (Frontiers in Plant Science, 2022)
CRISPR/Cas9-mediated genome editing has been demonstrated in the model diatom P. tricornutum, yet the currently available genetic tools do not combine the various advantageous features into a single, easy-to-assemble, modular construct that would allow the multiplexed targeting and creation of marker-free genome-edited lines. In this report, we describe the construction of the first modular two-component transcriptional unit system expressing SpCas9 from a diatom episome, assembled using the universal loop plasmid kit for Golden Gate assembly. We compared the editing efficiency of two constructs with orthogonal promoter-terminator combinations targeting the StLDP gene, encoding the major lipid droplet protein of P. tricornu-tum. Multiplexed targeting of the StLDP gene was confirmed via PCR screening, and lines with homozygous deletions were isolated from primary exconjugants. An editing efficiency ranging from 6.7 to 13.8% was ob-served in the better performing construct. Selected gene-edited lines displayed growth impairment, altered morphology, and the formation of lipid droplets during nutrient-replete growth. Under nitrogen deprivation, oversized lipid droplets were observed. The recovery of cell proliferation and the breakdown of lipid droplets were impaired after nitrogen replenishment. The results are consistent with the key role played by StLDP in the regulation of lipid droplet size and lipid homeostasis.